Acupuncture Treatment for Anxiety at Flowers Beauty Studio in Bandung - Afriyanti Bunga Mega Frawati; Ikhwan Abdullah; Amal Prihatono; Mayang Wulandari (CV. Publikasi Indonesia, 2026)
This study explores the effectiveness of acupuncture therapy in reducing anxiety symptoms accompanied by insomnia, a condition that has become increasingly prevalent globally and in Indonesia. Anxiety disorders significantly affect individuals’ quality of life, while limitations in conventional treatments and mental health services highlight the need for complementary therapeutic approaches. Therefore, this research aims to evaluate the benefits of acupuncture care in alleviating anxiety and improving sleep quality in patients. The study employed a qualitative case study design involving one adult female participant undergoing six sessions of acupuncture therapy over two weeks at Flowers Beauty Studio Bandung. Data were collected through observation, structured interviews, clinical examination based on Traditional Chinese Medicine (TCM) principles, and documentation. The therapy focused on balancing Yin deficiency and regulating Liver Qi stagnation through specific acupuncture points. The findings indicate a gradual and consistent improvement in the participant’s condition, including reduced anxiety levels, improved sleep duration and quality, decreased panic symptoms, and enhanced overall well-being. Clinical indicators such as pulse, tongue condition, and emotional stability also showed positive changes across therapy sessions. In conclusion, acupuncture therapy demonstrates effectiveness as a complementary and low-risk intervention for managing anxiety with insomnia. This approach contributes to restoring physical and emotional balance and offers a promising alternative for holistic mental health care.